Iowa RBA, September 8, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for September 8, 1997. Highlights of the update include the continued presence of Eurasian Collared Doves in Grinnell and sightings of Marbled Godwit and Red-necked Phalarope. Also included are handwritten notes for the next week's update with sightings of a Sabine's Gull, Purple Finches, and a Merlin. Epson - sheet feed/flatbed